Management of condylar resorption before or after orthognathic surgery: A systematic review. Issue 7 (July 2019) - He, Ze; Ji, Huanzhong; Du, Wen; Xu, Chunwei; Luo, En
Abstract: Background: Orthognathic surgery is a surgical procedure for the correction of maxillofacial deformities. The existence of condylar resorption before orthognathic surgery affects the selection of surgery time and plan. Besides, condylar resorption after orthognathic surgery often leads to the recurrence of deformities and affects the long-term effect of surgery. The purpose of this study was to perform a systematic review of the management of condylar resorption before or after orthognathic surgery. Methods: A systematic review of the scientific literature listed on PubMed, Embase, and Cochrane Controlled Trials Register was performed, up to October 2018. The outcome of the search was reviewed with a chart. Results: Ten articles with 180 patients were included in this study based on inclusion and exclusion criteria. We compared these studies to examine the effectiveness of the management of condylar resorption. Conclusion: The occurrence of condylar resorption can be influenced by complex factors. The management of condylar resorption before or after orthognathic surgery should base on the severity of condylar resorption. As the eligible studies with small sample sizes, heterogeneity in management method and outcome, high-quality clinical study concerning condylar resorption treatment is needed.